KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DALAM MENYELESAIKAN SOAL PISA MATEMATIKA PADA KONTEN BILANGAN - Dwi Putri; Attin Warmi (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2022)
Mathematical problem solving skills are one of the important skills that students have in learning mathematics. The purpose of this study is to describe students' mathematical problem-solving ability to solve PISA problems on quantity content. This research uses qualitative methods. The subjects in the study were students of class IX A SMPN 2 Tirtamulya. The data collection technique in this study is to provide a test in the form of two PISA Math problems. The results of this study are the average score of mathematical problem-solving skills of students classified into the medium category, which is 10.33. Students' mathematical problem-solving abilities in high categories meet the entire stage of problem solving, namely understanding problems, devising a plan, carrying out the plan, and looking back. The mathematical problem-solving ability of students in medium category is fulfilling the stage of devising a plan and carrying out the plan. Students' mathematical problem-solving abilities in low categories meet one of four stages, namely devising a plan.